Association between hyperuricemia and kidney stones in Southern China: a multicentre cross-sectional study - Zhong, Yuwen; He, Rongxin; Kang, Ganglin; Zhou, Zhongfang; Xiao, Kaimin; Li, Li (Frontiers in Endocrinology, 2026)
BackgroundHyperuricemia has been identified as a significant independent risk factor for kidney stones. However, a paucity of research has been conducted on the correlation between hyperuricemia in the general population and the prevalence of kidney stones. Southern China has a high incidence of kidney stones, and analysis of data from health check-ups can help to identify those at risk of developing kidney stones. This is of positive clinical significance for the prevention of kidney stones in hyperuricemia populations.MethodsA multicentre cross-sectional study was conducted using data from medical examination centres in four hospitals located in three southern Chinese provinces from 2022 to 2024. The analysis employed a combination of statistical methods, including logistic regression to identify independent risk factors for kidney stones in individuals with hyperuricemia. Additionally, a restricted cubic spline (RCS) method was utilised to examine the dose-response relationship between age, BMI, and serum uric acid levels and the risk of kidney stones. The study also employed a threshold effect analysis to identify the threshold inflection point between age and the risk of kidney stones.ResultsThe total health data of 2739 medical examiners were included in this study. The prevalence of kidney stones was found to be 25.48% (1.28% in females and 24.21% in males) in the hyperuricemia population. The application of logistic regression revealed that age, BMI, serum uric acid, sex, urine leukocyte abnormality, and urine erythrocyte abnormality functioned as independent risk factors, while water intake was identified as a protective factor. Furthermore, the results of the RCS indicated a nonlinear relationship between age and the prevalence of renal stones (P nonlinear < 0.001). Threshold effect results showed that for individuals under the age of 44, the risk of developing kidney stones increased by 6.3% with each additional year of age (P < 0.05).ConclusionIn the hyperuricemic population, age, BMI, serum annual acid, sex, abnormal leukocytes in urine and abnormal red blood cells in urine were identified as independent risk factors for developing kidney stones, while water intake was found to be a protective factor. The relationship between age and the development of kidney stones in hyperuricemia is non-linear.